THE ROLE OF INTELLECTUAL CAPITAL IN MODERATING HUMAN RESOURCE COMPETENCE ON THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN GORONTALO PROVINCE - Podungge, Robiyati; Monoarfa, Valentina; Eka, I Nengah Agus; Soleh, Nurdin (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to examine how intellectual capital moderates the relationship between human resource competencies and SME performance in Gorontalo Province. The research involved 381 SMEs spread across Gorontalo Province. Data analysis was conducted using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The results of the study indicate that human resource competencies have a positive and significant effect on SME performance, as evidenced by a t-value of 6.549 (greater than the t-table value of 1.96) and a significance value of 0.000 (less than 0.05). Furthermore, intellectual capital is also proven to have a positive and significant influence on SME performance, with a t-value of 4.141 (greater than 1.96) and a significance value of 0.000 (less than 0.05). Another important finding shows that intellectual capital strengthens the relationship between human resource competencies and SME performance, as indicated by a t-statistic value of 3.301 (greater than 1.96) and a significance value of 0.001 (less than 0.05).